Tikimybės veiksmažodžiai anglų ir lietuvių kalbose: atitikmenų paieška - Usonienė, Aurelija (Baltistica, 2006)
VERBS OF PROBABILITY IN ENGLISH AND LITHUANIAN: IN SEARCH OF EQUIVALENTS The paper looks at the qualitative and quantitative parameters of equivalence between English verbs of probability SEEM, APPEAR (LGSWE 1999: 708, 977) and their Lithuanian translation equivalents. The focus of the pilot study is on the following types of structures: English (BNC) Lithuanian (CCLL) JY0 1825 And they seemed to be old friends. CGE 887 She appeared a quick learner. Man atrodo, tebesu paauglė. Kol avižos auga, laukas atrodo žalias. The data for the translation corpus have been compiled from fiction (Rowling 2000), the British National Corpus (http://www.natcorp.ox.ac.uk/), the Corpus of the Contemporary Lithuanian Language and the Parallel English-Lithuanian corpus (http://donelaitis.vdu.lt), monolingual/bilingual dictionaries and grammar books. The purpose of the analysis is to compare the syntactic and semantic potential of the given verbs in the two languages to mark stance and to express speaker’s uncertainty. The paper aims to see what alternatives/decisions are preferred by translators and how much they are influenced by the source language, which might contribute to the discussion of the notion of equivalence in translation.